Sen and the art of quality of life maintenance: towards a general theory of quality of life and its causation - Ruta, D; Camfield, L; Donaldson, C (2007)
Sen's capability approach permits re-appraisal of a central concept in health and social care, and international development - 'quality of life' (QoL). We compare Sen's capability view of QoL with current views in health care, and re-define QoL as 'the gap between desired and actual capabilities'. A causal pathway linking resources to capabilities, and finally to QoL, is postulated. The notion of 'cognitive homeostasis' is introduced to explain the observed curvilinear relationship between resources and QoL. A separate set of factors is identified that act to sustain or destabilise QoL. We conclude by examining the model's implications for policy and evaluation.